The Histopathological Finding of the Surgically Extracted Atypical Dome-Shaped Choroidal Osteoma - Hirona Bessho; Hisanori Imai; Atsushi Azumi (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of atypical dome-shaped choroidal osteoma, which was diagnosed by histopathological finding of surgically extracted tumor. Case Report. A 35-year-old woman presented with visual field abnormality in the left eye (OS). Her best-corrected visual acuity with Landolt ring chart was 1.0 OS. The funduscopic examination revealed a yellowish dome-shaped choroidal tumor located in the temporal side of the macula with exudative retinal detachment. 25-gauge pars plana vitrectomy and the extraction of the tumor were performed for the definitive diagnosis. Results. As a result of histopathological finding from the extracted tumor, she was diagnosed with choroidal osteoma. 10 months after the last surgery, the BCVA is 0.7 OS. The tumor is not relapsed. Conclusions. We must keep in mind that choroidal osteoma can be one of the differential diagnoses for the dome-shaped choroidal tumor.